Approach of establishing the grinding population balance kinetic model for cassiterite-polymetallic sulfide ore. Issue 1 (20th July 2021) - Yang, Xiaojing; Ma, Shaojian; Jiang, Linling; Guo, Runnan
Abstract: The article provides the basic theory for adjusting and optimizing grinding of cassiterite-polymetallic sulfide ore, using ore from Guangxi China as the research object. The Julius Kruttschnitt drop weight test was adopted to establish the breakage distribution matrix for the ore with piecewise spline interpolation using MATLAB. Breakage and abrasion parameters were obtained from abrasion and single particle impact tests, and the core relationship established. Relationships of different degree of crush ( t 10 - t xx ) for different feed sizes were developed by simulating the t-family curves using Origin software, and breakage distribution matrix was derived from these relationships. The elements in the matrix model were calculated using a top-down method where each element in the matrix represents the parameter relating to a particular feed size. From batch grinding tests, the selection function was derived following a population balance model of discrete particles, and the analytical relationship between the selection function and grinding time was established. Thus, the particle-size distribution of ground product can be predicted, and was verified experimentally.